The Changes in Seed Germination Capacity, Seedling Growth, and Leaf Morphology of Ficus variegata Blume Influenced by Gamma-Ray Irradiation - Muhammad Zanzibar; Agus Astho Pramono; Yulianti; Kurniawati Purwaka Putri; Dede J. Sudrajat; Naning Yuniarti; Nina Mindawati; Dida Syamsuwida; Danu; Ratna Uli Damayati Sianturi; Y. M.M. Anita Nugraheni; Nurhasybi; Junaedi Ahmad (HAYATI Journal of Biosciences, 2023)
Gamma irradiation treatments have commonly been applied to induce variation in plant genetic improvement programs. The improvement of nyawai (Ficus variegata Blume) is urgently needed mainly to break the seed dormancy, increase seedling growth, and induce variation for selecting desired traits. This research aimed to assess the effect of gamma irradiation doses on seed germination, seedling growth, and leaf morphology of Ficus variegate Blume. This experiment's irradiation doses ranged from 5-240 Gy and were applied to seeds with varying levels of vigor based on the artificial seed aging process. The data displayed a positive relationship between low doses of gamma irradiation and the nyawai seed's endurance. Low irradiation doses, 5 to 30 Gy, are deemed capable of promoting seedling development, leaf retention, and diversity in leaf structure. The higher irradiation doses than 30 Gy decreased seedling growth, leaf number, and seedling survival. In addition, these doses also affect some morphological changes, including seedling height and leaf length and width.